Analgesia After Arthroscopic Rotator Cuff Repair: Subacromial Versus Interscalene Continuous Infusion of Ropivacaine. Issue 2 (1st March 2005) - Delaunay, Laurent; Souron, Vincent; Lafosse, Laurent; Marret, Emmanuel; Toussaint, Bruno
Abstract : Objectives: A continuous infusion of local anesthetic in the subacromial space has been shown to provide superior pain relief compared with placebo. This technique has been considered as an alternative to a continuous interscalene infusion. The aim of our study is to compare these 2 techniques for pain relief after arthroscopic rotator cuff repair. Methods: In a prospective randomized trial, 30 consecutive patients undergoing rotator cuff repair were included. An interscalene brachial plexus block was performed in all patients with mepivacaine 1.5% 30 mL. Then, 15 patients had an indwelling interscalene catheter inserted immediately after the block via a needle. Fifteen other patients had a subacromial catheter placed at the end of surgery by the surgeon. In both groups, a 2 mg/mL ropivacaine continuous infusion (5 mL/h) with PCA bolus (5 mL/30 min) was maintained for 48 hours. Pain was assessed in PACU and at 24 and 48 hours after surgery, at rest, and during passive motion. Total amount of oral morphine self-administered as rescue analgesia and cumulative 24-hour and 48-hour local anesthetic consumption were noted. Patient satisfaction and side effects were also noted. Results: Pain during motion in PACU (0 [0 to 60] v 40 [0 to 100] mm) and at 24 hours (10 [0 to 60] v 45 [20 to 100] mm), oral morphine (0 [0 to 6] v 3.5 [0 to 10] morphine capsules), and total amount of local anesthetic at 24 hours (122.5 [120 to 170] v 143 [129 to 250] mg) were lower in the continuous interscalene group. Local anesthetic side effects were less frequent in the continuous subacromial group. Satisfaction was comparable between groups. Conclusion: After arthroscopic rotator cuff repair, continuous interscalene block provides better analgesia compared with continuous subacromial infusion but with an increased incidence of minor side effects.